Patient and carer reports of care in metastatic presentation of cancer of unknown primary origin. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hughes, Philippa; Farrington, Clare; Brooks, David; Bath, Peter; Noble, Bill
Abstract : Background: Patient and caregiver experiences of cancer of unknown primary (CUP) have been under-researched. Common challenges include diagnostic uncertainty, poor prognosis and difficulty in identifying this population. Aims and methods: As part of a study to evaluate the development of a CUP team and pathway, we sought patient and carer viewpoints. Patients presenting with metastases of unknown primary origin were invited to complete questionnaires on symptoms, quality of life and care and to participate in semi-structured interviews, during two 6-month periods. A retrospective survey of all bereaved caregivers was conducted, using the VOICES (Views of Informal Caregivers-Evaluation of Services) questionnaire. Results: During two 6-month periods, 88 patients presented with CUP. Median time from presentation to death was 40 days. VOICES was sent to 71 bereaved carers, and 26 (36.6%) responded. Both good and bad care were reported, with primary care settings and hospital settings demonstrating variable practice in communication, control of pain and breathlessness and quality of care. Reports of hospice care were uniformly good. Where carers reported positive experiences of death at home they also reported effective home- care support. Of those patients well enough to be approached, 10 completed questionnaires and four were interviewed. Questionnaire data indicated a considerable symptom burden for some, particularly weakness/tiredness and pain. Interview themes included appreciation of the quality of care received, frustration at waiting for investigations and results, confusion as to who was leading care, distress at communication of bad news and difficulty in accepting the diagnosis of cancer. Conclusions: This small study highlights the distress experienced, but also demonstrates that good care is achievable. Palliative care has a particular contribution to make not only in optimising symptom control, but in addressing key issues associated with this cancer presentation: co-ordinating investigations and care, and providing skilled communication where diagnosis is uncertain.